Factors Affecting The Success Of Implementing Family Integrated Care For Adolescents Who Experience Bullying: A Literature Review - Nely Sofia Rahman; Dian Ramawati (Universitas Aisyah Pringsewu, 2023)
Background: Bullying is a negative action performed repeatedly by another person or a group against a certain individual. Various forms of bullying can be experienced by adolescents, such as verbal, physical, and relational bullying. Bullying has a significant negative impact on its victims. There is a consensus regarding the importance of family involvement in high-quality care. Family-centered care is expected to improve the quality of care for adolescent victims of bullying by involving families in nursing and medical intervention plans. Method: This is a literature review that uses PRISMA. The article search was conducted through electronic databases, including Pubmed, ScienceDirect, SAGE, and Google Scholar. The selected articles are published in the last ten years. The keywords used in this systematic review are “Bullying+Family Integrated Care+Adolescent”. Results: The article search did not yield results on the implementation of Family Integrated Care for adolescents who experience bullying. Family Integrated Care is more often used in NICU patients or pediatric patients who experience anxiety disorders during hospitalization. However, the authors found the application of Integrated Care and Family Centered Care in interventions for adolescent victims of bullying. There are seven selected articles, and they indicate a need for increased intervention involving family roles. Nurses can work with families to improve the quality and efficiency of care, as well as increase their knowledge and competence in caring for adolescent victims of bullying. Abstrak: Background: Bullying merupakan tindakan negatif yang dilakukan secara berulang oleh orang lain atau suatu kelompok terhadap individu tertentu. Berbagai bentuk bullying dapat dialami oleh remaja, seperti bullying verbal, fisik, dan relasional. Bullying menimbulkan dampak negatif yang signifikan terhadap korbannya. Pada saat ini, consensus umum mengenai pentingnya keterlibatan keluarga dalam perawatan yang berkualitas tinggi telah banyak dilakukan. Perawatan yang berpusat pada keluarga diharapkan dapat meningkatkan kualitas perawatan yang berfokus pada remaja korban bullying dengan melibatkan keluarga dalam rencana intervensi keperawatan dan medis. Metode: Penelitian ini merupakan studi kepustakaan dengan menggunakan PRISMA. Pencarian artikel menggunakan database elektronik, diantaranya Pubmed, Sciencedirect, SAGE, dan Google Scholar. Artikel yang digunakan adalah jurnal yang terbit dalam 10 tahun terakhir. Kata kunci yang digunakan dalam tinjauan sistematis ini yaitu “Bullying+Family Integrated Care+Adolescent”. Hasil: Dari hasil pencarian artikel, penulis belum menemukan penerapan Family Integrated Care pada remaja yang mengalami bullying. Penerapan Family Integrated Care lebih sering digunakan pada pasien NICU atau pasien anak yang mengalami gangguan kecemasan saat hospitalisasi. Tetapi, penulis menemukan penerapan Integrated Care dan Family Centered Care pada intervensi untuk remaja korban bullying. Terdapat 7 artikel yang terpilih dan perlu adanya peningkatan intervensi yang melibatkan peran keluarga. Perawat dapat bekerja sama dengan keluarga untuk meningkatkan kualitas dan efisiensi perawatan, serta meningkatkan pengetahuan dan kompetensi perawat dan keluarga dalam merawat remaja korban bullying.